Relationship between human serum albumin and in-hospital mortality in critical care patients with chronic obstructive pulmonary disease - Ling, Ma; Huiyin, Li; Shanglin, Chen; Haiming, Li; Zhanyi, Di; Shuchun, Wang; Meng, Bai; Murong, Lu (Frontiers in Medicine, 2023)
ABSTRACT: BACKGROUND: The relationship between human serum albumin levels and the prognosis of critical care patients with chronic obstructive pulmonary disease (COPD) remains controversial. OBJECTIVE: To investigate the relationship between serum albumin levels and in-hospital mortality in critical care patients with COPD. METHODS: This study used a retrospective observational cohort from the Medical Information in Intensive Care database (MIMIC-IV) in the United States. Multivariate Cox regression analysis was used to assess the relationship between serum albumin levels and in-hospital mortality. A restricted cubic spline line was also used to explore nonlinear relationship. RESULTS: A total of 3398 critical care patients with COPD were included. The overall in-hospital mortality was 12.4%. We found a negative relationship between human serum albumin and in-hospital mortality (HR = 0.97, 95% CI 0.96-0.99, P= 0.002). CONCLUSION: In critical care patients with COPD, there was a negative association between human serum albumin and in-hospital mortality.